METHODS OF PERMITTING SCHOOL STUDENTS (Physical Culture and Sport: Scientific Perspective, 2023)
The article is devoted to the study of ways of spending leisure time of students of grades 5-11 of a general secondary education institution. Leisure is an activity during free time from work or study, thanks to which an individual restores his ability to work and develops mainly those skills and abilities that cannot be improved in the field of work or study. Leisure time allows each individual to choose those types of activities that have properties that are absent in many types of work during working hours. Undoubtedly, leisure time plays an important role in the life of young people. The culture of children's leisure time has become a research interest relatively recently. However, there were not so many works on the study of schoolchildren's leisure activities. That is the relevance of our work. The purpose of the article is to investigate ways of spending leisure time of students of grades 5-11 of general secondary education institutions. In the study, we used the following research methods: theoretical analysis and generalization of literary sources; survey; methods of mathematical statistics. Results: we asked schoolchildren to indicate what they do in extracurricular time and offered to choose one option from the options offered (sports; physical education at the place of residence; watching TV; playing electronic games; visiting discos; working in the garden, classes on the computer, the Internet; reading fiction; communicating with friends; reading educational literature, preparing homework; additional education). The schoolchildren's answers were distributed as follows: in general, the highest percentage was given to the options - computer classes, Internet and communication with friends (21.3% each); the second step was taken by the count - I play electronic games (19.6%); 14.7% of schoolchildren each gave the option of sports and physical education at their place of residence, and the least percentage (8.1%) received the option of watching TV. The vast majority of respondents do not do homework on physical education (49.3%), 36.0% do it sometimes, 9.8% of schoolchildren indicated that they do not do homework on physical education, and 4.9% do it systematically. Answering the question of the questionnaire: "Do you exercise systematically in the sports section or on your own?", the vast majority of schoolchildren do not do physical exercises, both under the guidance of a coach and independently. A small percentage fell on the options: yes, I work out in the sports section and not systematically, but I work out. The fact that none of the respondents do physical exercises on their own is critical. The interviewed schoolchildren named the following types of sports or types of motor activity they are engaged in: sports games (football, basketball, volleyball, handball, tennis), martial arts (boxing, wrestling, karate), swimming, tourism, dancing, athletic gymnastics, athletics . In general, it can be stated that the majority of boys and girls did not participate in the organization and judging of competitions. Conclusions: methods of spending leisure time among schoolchildren aged 10-16 have been determined. They included: classes on the computer, the Internet, communication with friends, electronic games, sports and physical education at the place of residence, as well as watching TV.
Keywords: free time; students; physical culture; homework; sports sections